An anti-human immunodeficiency virus-negative pregnant woman was diagnosed with both cerebral venous sinus thrombosis and intracranial Cryptococcus simultaneously - Ren, Binbin; Guo, Yizhan; Chen, Kun; Chen, Lin (Journal of Emergency and Critical Care Medicine; Vol 2 (June 2018): Journal of Emergency and Critical Care Medicine, 2018)
Given the maternal physiological changes, the morbidity rate of cerebral venous thrombosis (CVT) is higher during pregnancy and puerperium. Intracranial cryptococcal infection is a severe central nervous system (CNS) infection caused by Cryptococcus which is mostly found in immunocompromised patients. Nevertheless, there was no report on human immunodeficiency virus (HIV)-negative pregnant woman presenting with both CVT and intracranial cryptococcal infection simultaneously. Here we present a case of CVT and intracranial cryptococcal infection on a HIV-negative pregnant woman who manifested recurrent headache.